1996
DOI: 10.1002/(sici)1097-010x(19961015)276:3<233::aid-jez7>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Regression of the epithelium in late previtellogenic follicles of Podarcis sicula: A case of apoptosis

Abstract: We investigated the reorganization of the follicular epithelium at the end of previtellogenesis in the lizard Podarcis sicula. In particular, we determined the mechanism of intermediate and pyriform cell regression and the fate of their different subcellular constituents. Morphological and biochemical analyses revealed the presence of hallmarks of apoptosis such as nuclear changes, chromatin condensation, protein scaffolds, RNA synthesis, and DNA fragmentation. It was therefore concluded that the remodelling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 0 publications
2
28
0
1
Order By: Relevance
“…In mammals, in particular, the presence of numerous gap junctions between granulosa cells (Albertini and Anderson, 1974), cumulus cells itself (Gilula et al, 1978), as well as between the oocyte and cumulus cells (Anderson and Albertini, 1976;Amsterdam et al, 1976;Gilula et al, 1978;Eppig, 1982;Simon et al, 1997), prompted the idea that gap junctions provide a support for oocyte growth, regulation of meiotic maturation, and, probably, for the transport of materials from the oocyte to granulosa cells (see for review: Buccione et al, 1990). Among vertebrates so far studied, intercellular bridges between follicle cells and the oocyte have been described only in previtellogenic follicles of squamate reptiles, (Ghiara et al, 1968;Neaves, 1971;Taddei, 1972;Hubert, 1971Hubert, , 1985Andreuccetti et al, 1978Andreuccetti et al, , 1979Laughran et al, 1981;Klosterman, 1987;Ibrahim et al, 1989;Andreuccetti, 1992;Motta et al, 1995Motta et al, , 1996, where they serve as channels allowing the flow of different cytoplasmic components to the oocyte during the whole previtellogenic phase (Motta et al, 1995). In this regard, the organization of squamate previtellogenic follicles is similar to Drosophila egg chambers, where intercellular bridges control the oocyte differentiation transporting different products from nurse cells to the oocyte (for review see: Miklos and Cooley, 1994).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In mammals, in particular, the presence of numerous gap junctions between granulosa cells (Albertini and Anderson, 1974), cumulus cells itself (Gilula et al, 1978), as well as between the oocyte and cumulus cells (Anderson and Albertini, 1976;Amsterdam et al, 1976;Gilula et al, 1978;Eppig, 1982;Simon et al, 1997), prompted the idea that gap junctions provide a support for oocyte growth, regulation of meiotic maturation, and, probably, for the transport of materials from the oocyte to granulosa cells (see for review: Buccione et al, 1990). Among vertebrates so far studied, intercellular bridges between follicle cells and the oocyte have been described only in previtellogenic follicles of squamate reptiles, (Ghiara et al, 1968;Neaves, 1971;Taddei, 1972;Hubert, 1971Hubert, , 1985Andreuccetti et al, 1978Andreuccetti et al, , 1979Laughran et al, 1981;Klosterman, 1987;Ibrahim et al, 1989;Andreuccetti, 1992;Motta et al, 1995Motta et al, , 1996, where they serve as channels allowing the flow of different cytoplasmic components to the oocyte during the whole previtellogenic phase (Motta et al, 1995). In this regard, the organization of squamate previtellogenic follicles is similar to Drosophila egg chambers, where intercellular bridges control the oocyte differentiation transporting different products from nurse cells to the oocyte (for review see: Miklos and Cooley, 1994).…”
supporting
confidence: 78%
“…Once formed, intercellular bridges appear as wide channels, filled by numerous cytoplasmic constituents such as mitochondria, ribosomes, whorl of membranes, and vacuoles. Such an organization is remarkably similar to that described in previtellogenic lizard follicles (Filosa, 1973;Andreuccetti et al, 1978Andreuccetti et al, , 1979Motta et al, 1995Motta et al, , 1996. In lizards, intercellular bridges first appear in follicles with double-layered follicular epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Durante esta etapa, en L. azarai, el epitelio folicular presentó marcados cambios estructurales pasando de ser una capa estratificada polimórfica a constituirse como una monocapa de células planas. Motta et al (1996) y Tammaro et al (2006, describen regresión de las células piriformes al final de la previtelogénesis por procesos de apoptosis. El adelgazamiento de la capa folicular durante la vitelogénesis observado en L. azarai podría deberse a eventos de apoptosis como lo postulan dichos autores.…”
Section: Discussionunclassified
“…H. mabouia, the granulosa becomes drastically reduced prior to the onset of the vitellogenesis (MOODLEY & VAN WYK 2007). It has been suggested that this reduction in size is associated with programmed cell death (apoptosis) (MOTTA et al 1996). Follicular atresia was characterized by a polymorphic granulosa layer, which consisted of large, irregular cells with circular to oval nuclei.…”
mentioning
confidence: 99%